Evaluation of the pathogenicity of Aschersonia aleyrodis on Bemisia tabaci in the laboratory and greenhouse - Zhang, Can; Ali, Shaukat; Musa, Peter Dennis; Wang, Xing-Min; Qiu, Bao-Li (Biocontrol science and technology, 2017)
The entomopathogenic fungus Aschersonia aleyrodis (Webber) is a promising fungal species against whiteflies. In this work, the pathogenicity of A. aleyrodis isolate Aa005 against MEAM1 Bemisia tabaci (Gennadius) was evaluated under laboratory and greenhouse conditions. The bioassay results indicated that the percentage of larval mortalities was concentration and age dependent. A. aleyrodis showed high pathogenicity against second and third instars and pupae with LC 50 values of 7.93 × 10 6 , 1.08 × 10 7 , and 1.56 × 10 7 conidia mL −1 , respectively. The median lethal time (LT 50 ) was lower (4.60 days) for second instars and was the highest (6.17 days) for pupae when inoculated with a concentration of 1 × 10 7 conidia mL −1 . Weekly sampling of immatures showed that the per cent mortality caused by A. aleyrodis at a conidial concentration of 1 × 10 7 conidia mL −1 was 71.21% in small nymphs, 69.31% in large nymphs and 53.36% in pupae. The dispersion index (DI) and Lloyd's Index of Patchiness (LIP) values indicated that the infected immatures had a tendency to aggregate. The study demonstrated that A. aleyrodis isolate A005 is an effective biocontrol agent for B. tabaci control under laboratory and greenhouse conditions.